Hydrogen desorption from hydride container under different heat exchange conditions - Andreasen, Gustavo Alfredo (2014)
The desorption behavior of a hydrogen storage prototype loaded with AB5H6 hydride, whose equilibrium pressure makes it suitable for both feeding a PEM fuel cell and being charged directly from a low pressure water electrolyzer without need of additional compression, was studied. The nominal 70 L hydrogen storage capacity of the container (T = 20 °C, P = 101.3 kPa) suffices for ca. 2.5 h operation of a 50 W hydrogen/oxygen fuel cell stack. The hydride container is provided with aluminum extended surfaces to enhance heat exchange with the surrounding medium. These surfaces consist of internal disk-shaped metal foils and external axial fins. The characterization of the storage prototype at different hydrogen discharge flow rates was made by monitoring the internal pressure and the temperatures of the external wall and at the center inside the container. The response of the storage device was tested at room temperature under different conditions such as natural convection in air and forced air ventilation, and at different temperatures in a thermostated water bath, representing possible real situations to feed hydrogen/oxygen fuel cells. Current results are discussed and correlated with each particular environmental condition and hydrogen flow rate. It is found that for some environmental conditions the flow rate discharge behavior improves significantly.